2001
DOI: 10.1046/j.1523-1755.2001.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of glucocorticoids in the maturation of the rat renal Na+/H+ antiporter (NHE3)

Abstract: These data demonstrate that glucocorticoids play a role in the postnatal maturation of the proximal tubule Na+/H+ antiporter activity and brush-border membrane NHE3 protein abundance. Glucocorticoid deficiency does not completely prevent the maturational increase in Na+/H+ antiporter activity and does not affect NHE3 mRNA abundance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 72 publications
2
36
1
Order By: Relevance
“…In these studies, we either prevented the maturational increase in glucocorticoids or thyroid hormone at a time well before the normal increase during postnatal development. We found that preventing the maturational increase in either thyroid hormone or glucocorticoids suppressed the maturational increase in Na + /H + antiporter activity and brush-border membrane NHE3 protein abundance without any effect on the basal level of NHE3 mRNA abundance (8,23). Furthermore, the rate of Na + /H + antiporter activity in both adrenalectomized and hypothyroid animals was higher than in neonates.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…In these studies, we either prevented the maturational increase in glucocorticoids or thyroid hormone at a time well before the normal increase during postnatal development. We found that preventing the maturational increase in either thyroid hormone or glucocorticoids suppressed the maturational increase in Na + /H + antiporter activity and brush-border membrane NHE3 protein abundance without any effect on the basal level of NHE3 mRNA abundance (8,23). Furthermore, the rate of Na + /H + antiporter activity in both adrenalectomized and hypothyroid animals was higher than in neonates.…”
mentioning
confidence: 81%
“…The maturational increase in these hormones parallels the maturational increase in NHE3 (36), the predominant Na + /H + antiporter isoform on the apical membrane of the proximal tubule (15, 40, 41), and Na + /H + antiporter activity (36). We examined previously the role of glucocorticoids and thyroid hormone in mediating the increase in Na + /H + antiporter activity (8,23). In these studies, we either prevented the maturational increase in glucocorticoids or thyroid hormone at a time well before the normal increase during postnatal development.…”
Section: Nhe3; Adrenalectomy; Renal Development; Microperfusion; Cell Phmentioning
confidence: 99%
“…The cortex was homogenized with 20 strokes of a Potter-Elvehjem homogenizer at 4°C. BBMV were then isolated by differential centrifugation and magnesium precipitation as described (32). The final BBMV fraction was resuspended in isolation buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Brush border membrane proteins (25 g per lane) were denatured and then separated on a 7.5% polyacrylamide gel by using SDS͞PAGE as described (32). The proteins were transferred overnight to a poly(vinylidene difluoride) membrane at 120-140 mA at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…It is unclear whether the findings in our studies in the rabbit had any general applicability to rodents or other species. Furthermore, the rabbit has limitations in the study of renal development, because they do not survive adrenalectomy, a procedure often used in studying postnatal development (14,15). In the present rat proximal tubule in vitro microperfusion flux study, we examine some of the developmental permeability properties in rats to determine whether our previous studies in rabbits have any applicability to other species.…”
mentioning
confidence: 99%